Malawi - Travel and Tourism : Realizing the Potential - World Bank (World Bank, 2012)
Malawi sits amid a vibrant Travel and Tourism (T&T) region that is growing rapidly and increasing its world market share. Proximate to countries with thriving T&T sectors, Malawi has a relatively underdeveloped diversity of natural, cultural, and man-made attractions. It is challenged to embrace effective policies that will enable public and private sector alignment to achieve a viable niche as an economically productive, multi experience destination in its own right. It is important to view tourism as a national priority across sectors and ministries in Malawi. Thus, there is the need to better understand the economic potential of Malawi's T&T sector and recommend strategies to promote a level of competitiveness that leads to further economic growth, employment generation, and poverty reduction. The goal is to identify the economic potential of T&T in Malawi. The objective of T&T in Malawi is to delivering economic growth and diversification is to analyze the value of T&T in Malawi.